The Role of Reflection in the Effects of Community Service on Adolescent Development: A Meta‐Analysis. Issue 6 (24th July 2014) - van Goethem, Anne; van Hoof, Anne; Orobio de Castro, Bram; Van Aken, Marcel; Hart, Daniel
<x xml:space="preserve">Abstract</x> This meta‐analysis assessed the effect of community service on adolescent development and the moderation of this effect by reflection, community service, and adolescent characteristics to explicate the mechanisms underlying community service effects. Random effects analyses, based on 49 studies (24, 477 participants, 12–20 years old), revealed that community service had positive effects on academic, personal, social, and civic outcomes. Moderation analyses indicated that reflection was essential; the effect for studies that include reflection was substantial (mean ES = .41) while community service in the absence of reflection yielded negligible benefits (mean ES = .05). Effects increased when studies include more frequent reflection and community service, reflection on academic content, and older adolescents. These findings have implications for understanding and improving community service.